A review: studying the effect of graphene nanoparticles on mechanical, physical and thermal properties of polylactic acid polymer. Issue 6 (27th January 2023) - Dehnou, Kianoush Hatami; Norouzi, Ghazal Saki; Majidipour, Marzieh
Abstract : Polylactic acid (PLA) is a linear aliphatic polyester thermoplastic made from renewable sources such as sugar beet and cornstarch. Abstract : Polylactic acid (PLA) is a linear aliphatic polyester thermoplastic made from renewable sources such as sugar beet and cornstarch. Methods of preparation of polylactic acid are biological and chemical. The advantages of polylactic acid are biocompatibility, easily processing, low energy loss, transparency, high strength, resistance to water and fat penetration and low consumption of carbon dioxide during production. However, polylactic acid has disadvantages such as hydrophobicity, fragility at room temperature, low thermal resistance, slow degradation rate, permeability to gases, lack of active groups and chemical neutrality. To overcome the limitations of PLA, such as low thermal stability and inability to absorb gases, nanoparticles such as graphene are added to improve its properties. Extensive research has been done on the introduction of graphene nanoparticles in PLA, and all of these studies have been studied. In this study, we intend to study a comprehensive study of the effect of graphene nanoparticles on the mechanical, thermal, structural and rheological properties of PLA/Gr nanocomposites and also the effect of UV rays on the mechanical properties of PLA/Gr nanocomposites.